-8r+27=-4(-7-r)-1

Simple and best practice solution for -8r+27=-4(-7-r)-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8r+27=-4(-7-r)-1 equation:


Simplifying
-8r + 27 = -4(-7 + -1r) + -1

Reorder the terms:
27 + -8r = -4(-7 + -1r) + -1
27 + -8r = (-7 * -4 + -1r * -4) + -1
27 + -8r = (28 + 4r) + -1

Reorder the terms:
27 + -8r = 28 + -1 + 4r

Combine like terms: 28 + -1 = 27
27 + -8r = 27 + 4r

Add '-27' to each side of the equation.
27 + -27 + -8r = 27 + -27 + 4r

Combine like terms: 27 + -27 = 0
0 + -8r = 27 + -27 + 4r
-8r = 27 + -27 + 4r

Combine like terms: 27 + -27 = 0
-8r = 0 + 4r
-8r = 4r

Solving
-8r = 4r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-4r' to each side of the equation.
-8r + -4r = 4r + -4r

Combine like terms: -8r + -4r = -12r
-12r = 4r + -4r

Combine like terms: 4r + -4r = 0
-12r = 0

Divide each side by '-12'.
r = 0

Simplifying
r = 0

See similar equations:

| 3(w-1)=-12 | | 4+16x=7x+40 | | ln(9x+80)=ln(8x+71) | | 4(-7n-5)=12+4n | | 2x^2+8x-x-4=18 | | 4x+20=2x+25+x+20 | | 3x+4y=6.8 | | X-512=487 | | 40-6x=-90x+40 | | -53=n+7 | | X^2+2xy=-8 | | 9(4-6)+55= | | -15.00-2.00x=25.00 | | f(x)=5x^2+10x+3 | | -15.00-12.00x=25.00 | | 5.75=3/4x | | -7(r-9)= | | 5(2x+3)=4x-9 | | 6r+5(4r-12)= | | 7+7x=2x+32 | | 85=m-4 | | 43+10n=24n-27 | | (x-4y)dx+(x+2y)dy=0 | | 4.8/2 | | 2.5/465 | | 7(5n+9)+n= | | h(t)=27 | | Log(8)+log(-5x)=1 | | -5m+45=27-7m | | 7x-10=6(11-3x) | | 4x-11=9x-26 | | 18-3=15 |

Equations solver categories